Carl Jung’s archetypes in Malayalam film: a case study on the film ‘Urumi’ - Varghese, Sona; Balasubramanian, Arumugam (2017)
Movies are the visual- auditory symbolic narrative that explains the living reality of people. Films employ Carl Jung’s concept of archetypes-prototypical characters.This research provides an insight about the theory of archetype based on the assumption that archetypes resides deep inside human mind.The researcher proposes that the Malayalam film industry in India showcases the western concept of archetype using the movie Urumi as a case study. For this study, different clips are taken from the movie to represent six essential archetypes, namely, Hero, Anima, Animus, Mentor (sage), Shadow, and Trickster.The psychoanalysis of this movie carried out in this paper provides evidence for the existence of all six essential archetypes identified by Carl Jung. Thus this article will be a fruitful resource for future research in the field of psychoanalysis of movies.